Family violence against children: intervention of nurses from the Family Health Strategy - Kelianny Pinheiro Bezerra; Akemi Iwata Monteiro (Universidade Federal do Ceará, 2012)
This study Aimed to analyze the performance of nurses of the Family Health Strategy by facing family violence against children and identifying actions to prevent the problem. It is a descriptive and exploratory research with qualitative feature, whose data were analyzed according to content analysis. 14 nurses from the Family Health Strategy of Mossoró-RN took part in the Study. Data were collected using a semi-structured questionnaire. Health promotion actions are educational activities developed after detecting the problem. Fear of reprisals by the offending agent, work overload, lack of managerial support and the difficulty for the accomplishment of interdisciplinarity, intersectorality and comprehensive care were mentioned as barriers to the confrontation of the problem.